Man-machine interaction-based phenotyping preprocedurally identifies patients with severe aortic stenosis, who will not recover from cardiac damage following transcatheter aortic valve replacement. (3rd October 2022) - Rippen, E; Lachmann, M; Schuster, T; Xhepa, E; Von Scheidt, M; Harmsen, G; Yuasa, S; Kupatt, C; Joner, M; Laugwitz, K L
Abstract: Background: Severe aortic stenosis (AS) can lead to left heart dysfunction, pulmonary hypertension (PH), and eventually right heart failure. Clinical phenotypes therefore appear heterogeneous, depending on disease progression and comorbidities. Purpose: This study therefore sought to improve diagnostic and prognostic resolution in patients undergoing transcatheter aortic valve replacement (TAVR) for severe AS by developing a man-machine interaction-based phenotyping approach. Methods: Unsupervised agglomerative clustering was applied to preprocedural data from echocardiography and right heart catheterization from 366 consecutively enrolled patients undergoing TAVR for severe AS. Echocardiographic follow-up data, obtained on day 147±75.1 after TAVR, were available from 247 patients (67.5%). Results: Cluster analysis revealed four distinct phenotypes, reflecting various extents of disease severity, and hence differing in mortality. Patients from cluster 1 presented with preserved left ventricular ejection fraction (LVEF; 57.2±6.4%) and with normal mean pulmonary artery pressure (mPAP) levels (21.2±6.5 mmHg). In contrast, patients in cluster 2 suffered from postcapillary PH (mPAP: 34.2±7.8 mmHg). Left heart failure (LVEF: 42.4±15.7%), severe PH (mPAP: 46.9±8.5 mmHg), and right heart dysfunction (tricuspid annular plane systolic excursion [TAPSE]: 16.1±4.57 mm) characterized patients in cluster 3. Patients from cluster 4 showed mild postcapillary PH (mPAP: 27.5±9.2 mmHg), yet dilatation of all heart chambers, biventricular dysfunction (LVEF: 47.3±12.2%, TAPSE: 16.8±4.5 mm), and a high prevalence of both mitral and tricuspid regurgitation (12.5% and 14.8%, respectively). Correction of severe AS by TAVR significantly reduced the proportion of patients suffering from concurrent severe mitral regurgitation (from 9.29% to 3.64%, p-value: 0.0015). Moreover, pulmonary artery pressures were ameliorated (estimated systolic pulmonary artery pressure: from 47.2±15.8 mmHg to 43.3±15.1 mmHg, p-value: 0.0079). However, right heart dysfunction as well as the proportion of patients with severe tricuspid regurgitation remained unchanged. Clusters 3 and 4 with persistent right heart dysfunction ultimately displayed 2-year survival rates of 69.2% (95% CI: 56.6–84.7%) and 74.6% (95% CI: 65.9–84.4%), which were significantly lower compared to clusters 1 and 2 with little or no persistent cardiopulmonary impairment (88.3% [95% CI: 83.3–93.5%] and 85.5% [95% CI: 77.1–94.8%]). Conclusion: This phenotyping approach preprocedurally identifies patients with severe AS, who will not recover from extra-aortic valve cardiac damage following TAVR and whose survival is therefore significantly reduced. Importantly, not the degree of PH at initial presentation, but the irreversibility of right heart dysfunction determines prognosis. Funding Acknowledgement: Type of funding sources: None.